2013
DOI: 10.1161/circgenetics.113.000122
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Ventricular Arrhythmias With Genotype in Arrhythmogenic Right Ventricular Cardiomyopathy

Abstract: A total of 90 unrelated Chinese subjects with definite (n=69), borderline (n=15), or possible (n=6) diagnosis of ARVC and 300 age-, sex-, and ethnicity-matched healthy control subjects were recruited for gene analysis at our center. ARVC was diagnosed in all patients according to the revised diagnostic Task Force Criteria. 17 None of the control subjects had a history of cardiovascular or other systemic diseases.This study was performed in accordance with the principles of the Declaration of Helsinki and appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 29 publications
3
42
2
Order By: Relevance
“…The electrocardiography was characterized as a QRS wave duration ≥110 ms, inverted T waves in V 1 -V 3 leads, and completed left bundle brock [19]. In a Chinese cohort enrolling 90 subjects with ARVC/D, 5 patients carried the DSG2 p.F531C mutation [20]. In a Japanese family with ARVC, 2 probands carried compound DSP and DSG2 mutations (DSP p.K1582E and DSG2 p.F531C), whereas another member of this family, who satisfied 1 major criteria, carried only 1 mutation of DSP p.K1582E.…”
Section: Discussionmentioning
confidence: 99%
“…The electrocardiography was characterized as a QRS wave duration ≥110 ms, inverted T waves in V 1 -V 3 leads, and completed left bundle brock [19]. In a Chinese cohort enrolling 90 subjects with ARVC/D, 5 patients carried the DSG2 p.F531C mutation [20]. In a Japanese family with ARVC, 2 probands carried compound DSP and DSG2 mutations (DSP p.K1582E and DSG2 p.F531C), whereas another member of this family, who satisfied 1 major criteria, carried only 1 mutation of DSP p.K1582E.…”
Section: Discussionmentioning
confidence: 99%
“…The inheritance pattern of AC is more complex than previously appreciated, with frequent requirement for more than one 'hit' for fully penetrant disease [60,61,66,67]. The low penetrance of AC may be explained by a "recessive-like" inheritance pattern, based on the fact that AC probands often carry homozygous or compound heterozygous variants in the same gene, or digenic/oligogenic variants in a cluster of desmosomal genes.…”
Section: Ac Genes/mutations and Diagnostic Implicationsmentioning
confidence: 99%
“…Recent studies have shown that stop-coding in diseasecausing genes are more pathogenic than missense mutations, since the former are causing alteration of protein length and conformation, leading to haploinsufficiency due to protein instability [67][68][69][70]. Entire PKP2 exons or even whole gene deletions have been recently described in AC families with a frequency of approximately 2 % [71][72][73].…”
Section: Ac Genes/mutations and Diagnostic Implicationsmentioning
confidence: 99%
“…ARVC is a prime example of a cardiac disease associated with mutations/defects in desmosomal cell-cell junction components leading to defects in cardiac conduction, which include specific defects in the His-Purkinje system (Zusterzeel et al, 2013, Quarta et al, 2011, Bae et al, 2013, Bao et al, 2013, Cox et al, 2011) (Table 2). The electrophysiological criteria for diagnosing ARVC include epsilon waves, late potentials, prolonged terminal activation duration, ventricular tachycardia, and extrasystoles (Marcus et al, 2010).…”
Section: Ccs Defects Found In Human Patients With Underlying Defementioning
confidence: 99%